Respuesta :

Answer:

[tex]f(-5)=62[/tex]

Step-by-step explanation:

One is given the following function:

[tex]f(x)=3x^2+3x+2[/tex]

One is asked to evaluate this function for (f(-5)). Substitute (-5) in place of (x) and simplify to evaluate. Remember the order of operations when simplifying. The order of operations is the sequence by which one is supposed to perform operations in an equation. This sequence of the following:

  1. Parenthesis
  2. Exponents
  3. Multiplication or Division
  4. Addition or Subtraction

Use this systematic method of problem-solving in this equation. Simplify terms based on their place in the order of operations, and not on their place in terms of their placement in the equation.

[tex]f(x)=3x^2+3x+2[/tex]

[tex]f(-5)=3(-5)^2+3(-5)+2[/tex]

[tex]=3(25)+3(-5)+2[/tex]

[tex]=3(25)-15+2[/tex]

[tex]=75-15+2[/tex]

[tex]=60+2[/tex]

[tex]=62[/tex]